Code-Switching Varieties in Syrian Community : (A Case Study in Syria and Turkey) - Mohammad Umar Muslim; Nouran Alfashtakie (Hasanuddin University, 2022)
The main focus of this study is the way code-switching is used in the Syrian community. The study is designed to examine the patterns of code-switching in communication among the young generation and adults as well. It encompasses bilingual and multilingual Syrian participants, young and adult, both in Syria and Turkey. Therefore, factors like migration experience and age will be explored. For this purpose, data are taken from conversations with participants via voice calls; all recorded conversations were transcribed and transliterated to clarify the code-switching patterns. The Mixed Methods Approach to analyze participants’ data based on Muysken's code-switching typology and the three-way division is adopted. The findings yielded that 7 participants exhibited no code-switching at all versus 9 who did and that the insertional division is the one prevailing in almost all instances of code-switching. The results suggest that age is a prominent factor in the process of CS, while cultural exposure is not. It is also observed that although a small difference is detected between genders, it is not an affecting one.